TINJAUAN HUKUM ISLAM TENTANG PENCEGAHAN BUDAYA KEKERASAN TERHADAP ISTRI - Suhadak, Faridatus (EGALITA, 2012)
Indonesia tries to eliminate domestic violence by issuing Act Number23,2004 on domestic violence elimination. It aims at to build happy andprosperous Indonesian society particularly in small context that is family.Indonesian society consists of muslim as the majority. It influences on theway of life of the society for state law and Islamic law including family law.This paper tries to discuss family problem namely spouse’s relationship inIslamic law perspective. The focus of this discussion is spouse’s relationshipin form of domestic violence within its context of which cultural-based understanding as the factor of domestic violence.